Evaluation of the accuracy of the mechanical torque wrench by the number of uses and ratchet type - Karaman, Tahir; Kahraman, Onur Evren; Eser, Bekir; Altintas, Eyyup; Yildirim, Tuba Talo; Oztekin, Faruk (Mosher & Linder, Inc, 2019)
Purpose: To evaluate the accuracy of mechanical torque rachet types based on the number of uses. Methods: A total of 25 ratchets, including three frictional- and two spring-type torque ratchets from every mechanical torque ratchet group, were used in our study. A digital torque measurement device was used in assessing the efficiency of mechanical torque ratchets. All ratchets were tightened according to the torque values recommended by the companies. The ratchets were tightened 500 times in total. Results: Given the changes in torque delivery by the number of uses, a statistically significant torque loss was observed in the Bego ratchets (P<0.05), and a statistically significant increase was found in the torque values of the other ratchet groups (P<0.05). The highest increase in torque values was obtained in the MEDENTIKA ratchet group.
Keywords: Fixed Dental Prostheses; Limiting Devices; Complication Rates; Observation Period; Style